The Impacts of Bullying to the Main Character in the Movie Carrie - Dwi Wulan Cahya Ningrum; Syaiful Bahri (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
In this research, the researcher identified the types of bullying and described the impacts of bullying to the main character in movie Carrie. The data in this research are in the form of utterances and actions that contains bullying in movie Carrie. This research was done by analyzing the data qualitatively. Here are the steps to analyze the data; 1) identifying or classifying data based on the types of bullying by The National Centre Againts Bullying (2019), 2) describing impacts of bullying used theory of Ken Righby in Can J Psychiatry (2003), and 3) making the conclusion based on the types and impacts of bullying in movie Carrie. The finding of the research showed that there were three impacts of bullying on the main character in movie Carrie: low psychological well-being, poor adjustment, and psychological distress. Low psychological well-being was the most dominant impact of bullying occurred in movie Carrie. There were four types of bullying found in movie Carrie: physical bullying, verbal bullying, social bullying, and cyber bullying. Verbal bullying was the most dominant type of bullying found in movie Carrie.